Exploring the representation of Women in the local election process: the case study of Gresik regency in the 2024 - Alifah El Karimah (POLTRANS: Journal of Politics and Social Transformation, 2025)
The phenomenon of subversion against women in the selection process for regional head candidates in Gresik Regency in the 2024 is evidence that women's representation in local politics still faces serious challenges. This research was motivated by the case of Bu Min, an incumbent deputy regent candidate who was not re involved in the regional elections, despite having a track record in bureaucracy and political legitimacy. The issue raised in this study is how subversive political practices occur systematically and covertly through informal mechanisms, such as party elite domination, accommodation of central regional interests and masculine political culture. This study analyses how institutional subversion against women occurs in the regional head selection process and to what extent political parties perpetuate gender exclusion in local politics. Using a qualitative descriptive approach and case study method, this research finds that the hierarchical and non transparent internal structure of political parties, as well as weak commitment to gender equality, are the main factors driving the marginalisation of women. This study contributes to understanding the relationship between power, gender, and local democracy. It underscores the need to reform the political selection system to make it more fair and inclusive of women's leadership.